THE MAIN PROPERTIES AND EVOLUTIONARY FEATURES OF ANTIFREEZE PROTEINS - L. L. Bildanova; E. A. Salina; V. K. Shumiy (Вавиловский журнал генетики и селекции, 2014)
Antifreeze proteins are a class of proteins synthesized by poikilothermic organisms under cold stress. These proteins have random phylogenetic distribution, differ in primary and secondary structures, have different regulatory pathways, but they all display a common feature: the ability to be adsorbed onto the surface of ice crystals and to modify their growth. The review summarizes data on the origin of antifreeze proteins, activities and mechanisms mediating their action with emphasis on cereals, including wheat.